Mathematics for matriculation - Abdul Hadi Yaakub 1958-; Ong, Beng Sim; Yong Zulina Zubairi; Tan, Chong Eng; Lye, Min Soon; Lee, Khaik Yong; Che Noorlia Noor; Maheran Nuruddin (Oxford Fajar Sdn Bhd, 2015)
Mathematics for Matriculation Semester 2 Fourth Edition Updated is a comprehensive coursebook written for students studying Mathematics in local matriculation colleges. It is based on the Matriculation Mathematics QS025 syllabus issued by the Matriculation Division, Ministry of Education, Malaysia. This coursebook aims to stimulate students' interest in mathematics and help them gain a firm understanding of important principles and concepts in mathematics. In addition, it helps students prepare for their Mathematics examination.